Whole genome sequencing reveals novel mutations causing autosomal dominant inherited macular degeneration. (2nd November 2018) - Borooah, Shyamanga; Stanton, Chloe M.; Marsh, Joseph; Carss, Keren J.; Waseem, Naushin; Biswas, Pooja; Agorogiannis, Georgios; Raymond, Lucy; Arno, Gavin; Webster, Andrew R.
ABSTRACT: Background : Age-related macular degeneration (AMD) is a common sight threatening condition. However, there are a number of monogenic macular dystrophies that are clinically similar to AMD, which can potentially provide pathogenetic insights. Methods : Three siblings from a non-consanguineous Greek-Cypriot family reported central visual disturbance and nyctalopia. The patients had full ophthalmic examinations and color fundus photography, spectral-domain ocular coherence tomography and scanning laser ophthalmoscopy. Targeted polymerase chain reaction (PCR) was performed as a first step to attempt to identify suspected mutations in C1QTNF5 and TIMP3 followed by whole genome sequencing. Results : The three patients were noted to have symptoms of nyctalopia, early paracentral visual field loss and, in older patients, central vision loss. Imaging identified pseudodrusen, retinal atrophy and RPE-Bruch's membrane separation. Whole genome sequencing of the proband revealed two novel heterozygous variants in C1QTNF5, c.556C>T, and c.569C>G. The mutation segregated with disease in this family, occurred in cis, and resulted in missense amino acid changes P186S and S190W in C1QTNF5. In silico modeling of the variants revealed that the S190W mutations was likely to have the greatest pathologic effect and that the combination of the mutations was likely to have an additive effect. Conclusions : The novel mutations in C1QTNF5 identified here expand the genotypic spectrum of mutations causing late-onset retinal dystrophy.